A Simple Intervention to Decrease Nutrient Losses in Continuous Feeds With Human Milk. Issue 4 (April 2020) - Davidson, Jennifer; Elabiad, Mohamad T.
ABSTRACT: Objectives: Current evidence suggests that a significant amount of human milk fat is lost because of tubing adsorption. The objective was to evaluate the effect of reintroducing tubing leftover milk on the quality of macronutrient content of delivered milk. Methods: This was an in vitro study. The standard method of preparing and delivering fortified human milk includes preparing a small extra volume that would be used for priming the connection tubes. At the end of the infusion, the tubes and any milk leftover would be discarded. This method was compared with a new method where by the exact milk volume was prepared and used to prime the connection tubes. Leftover tubing milk was pushed with air. Results: The standard method was associated with significant losses in fat, protein, and calories of 16.7%, 3.4%, and 9.2% compared with the new method of 8.2%, 0%, and 3.3%, respectively. These losses in the standard method were predominantly explained by the significant gains in the left over milk contents of fat 6.3 ± 1.1 g/dL, protein 3.5 ± 0.4 g/dL, and calories 28 ± 2.6 kcal/oz as compared with prepared milk of 4.8 ± 0.3, 2.9 ± 0.3 g/dL, and 24.0 ± 0.8 kcal/oz respectively, P  = 0.002. Conclusions: Traditional continuous delivery methods of human milk are associated with significant losses of fat and protein. By preparing the exact amount of ordered milk and then pushing through the residual milk left in the tubing with a small amount of air, this study offers a simple intervention that would significantly decrease these losses.